(3OjhGf GdMGLQjs - (3MSGe GdOjf Hf YjSi Hf SfLQ Hf HgQGe Hf LHQjd GdEQHdj GdeYQha H` GdMGLQi,J (B639 (3g` s ((3Cejf Hf NjQ Gddg GdYeQj s)
(3ChdgG (B:s
(3bGd GdCejQ GdHGQY GdeYQha HGdMGLQj hcGfJ haGJg bGd GdeDda dgPG GdOjhGf (B((3GdLGeY dg(B) (3hgh SHjd GdhGba Ydi gPG GdOjhGf GdUaM YeG jLOg ef GdNWC hGdRdd s
(3BNQgG (B:s
(3jG ef HMSf LeGdh egLJj CeQV hef EPG CYQrV dMJbj hdLaG YQV bO UM Cf GdbeQ ef MSfc ESJbQV hGdhLg efc dCQHGH Gdghi MQV s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3GfXQgG eY OjhGf GHf GdfHjgs
(3fSNI NGeSIs
(3JfbU GdaUdjf GdCNjQjf hgeG eG bGdg ef GdehGdjG heG bGdg ef GdOhHjJs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs